2003
DOI: 10.1002/ejic.200200602
|View full text |Cite
|
Sign up to set email alerts
|

NIR Dyes Based on [M(R,R′timdt)2] Metal‐Dithiolenes: Additivity of M, R, and R′ Contributions To Tune the NIR Absorption (M = Ni, Pd, Pt; R,R′timdt = Monoreduced Form of Disubstituted Imidazolidine‐2,4,5‐trithione)

Abstract: With the aim of preparing new dyes for Q‐switching and/or mode‐locking Nd‐based lasers, such as Nd:YLF and Nd:YAG (emission wavelengths 1053 and 1064 nm, respectively), the syntheses of about 30 new neutral dithiolenemetal complexes belonging to the class [M(R,R′timdt)2] have been carried out [M = Ni (4a−c; 4g−j), Pd (5a−j), Pt (6a−j); R,R′timdt = monoreduced form of disubstituted imidazolidine‐2,4,5‐trithione]. The examination of the effects induced on the intense NIR absorption by changing M, R, and R′ has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 35 publications
2
28
0
2
Order By: Relevance
“…[16Ϫ24] Hybrid-DFT [18,19,23] and very recent TD-DFT calculations [21,24] confirmed that the tight HOMOϪLUMO energy gap is responsible for the low-energy NIR transition falling at about 1000 nm (extinction coefficients as high as 120000 …”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…[16Ϫ24] Hybrid-DFT [18,19,23] and very recent TD-DFT calculations [21,24] confirmed that the tight HOMOϪLUMO energy gap is responsible for the low-energy NIR transition falling at about 1000 nm (extinction coefficients as high as 120000 …”
Section: Introductionmentioning
confidence: 77%
“…[17] Synthesis of [M(R,RЈtimdt) 2 ]·nI 2 Adducts: The dithiolene complexes [M(R,RЈtimdt) 2 ] (M ϭ Ni, Pd, Pt; R ϭ RЈ ϭ Et; R ϭ Me, RЈ ϭ iPr) were synthesised as reported previously. [18,19,23] They (15Ϫ30 mg) were then reacted with weighed amounts of diiodine in 1:1, 1:2, 1:5, and 1:10 molar ratios, in 30 mL of CHCl 3 /hexane mixtures (1:3 v/v) according to the procedure described previously for the reaction between 8 and Br 2 . [22] The stoichiometric ratios of the final products summarised in Scheme 1 were calculated on the basis of the elemental analyses.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations